Some aspects of the formation of legal framework of the Eurasian Economic Union - Amirbek, K.S. (Bulletin of the Karaganda University “Law Series”, 2018)
The task to examine the major issues of the legal framework formation of the new Union Association of States — the Eurasian Economic Union (EAEU) is put in this article. Today EAEU becomes the most important subject of foreign economic activity in the global economy. Eurasian Union is a full–fledged single market (with certain restrictions) with the generated system of instruments of legal regulation of its activities. Measures of regulating of foreign economic activities of the Union and its individual members form the basis of unified foreign activity. The author reveals some aspects of the theory of Eurasian integration, examines the political and the legal nature of the EAEU. Particular attention is drawn to the formation of the legal base of the EAEU, analyzes the meaning and structure of the legal framework of the EAEU. On the base of analysis of international experience of the name of legal acts inconsistencies and contradictions in the title of the sources of law EAEU according to international law and scientific doctrine revealed by the author. The author notes that internal economic systems of sovereign subjects of international law are to interact with each other are united among themselves in the Common Economic Space, which is the manifestation of the globalization of international economic sphere. The relationship of domestic economies in different parts of the international community, go with different speeds is discussed in this work. If in different states disintegration processes are developing rapidly, then in certain territories the sovereign subjects of international law are taking a strategic course for accelerated domestic economic relations.